In vitro Micropropogation of Endangered Orchid Aerides odotrata Lour. from Seed Culture - Thapa, Mahendra; Maharjan, Lasta; Chaudhary, Tej Lal; Chaudhary, Nima; Joshi, Pusp Raj (Journal of Nepal Biotechnology Association, 2026)
Aerides odorata Lour. is an endangered orchid, famous for its appealing, fragrant blooms and its epiphytic growth. This study examined the effects of culture medium composition, plant growth regulators, and organic additives on the in vitro growth of Aerides odorata Lour. Full-strength MS medium enriched with 10% coconut water produced the highest seed germination rate (85%), showing earlier protocorm and shoot development in comparison to other strength of MS medium and medium with plant growth regulators. Shoot multiplication was found a notable increase with 2.0 mg/l of BAP, yielded the highest shoot count (13.4 per explant), whereas shoot elongation was most effective in MS medium with 1.0 mg/l of BAP and 0.1 mg/l of NAA. The effective of root number induction was showed the highest in MS medium with NAA and IBA at 3 mg/l, while root length induction was in MS medium with IBA at 3 mg/l, highlighting its prolonged auxin effectiveness. The results emphasize the combined effect of coconut water, BAP and IBA in enhancing effective micropropagation of A. odorata, offering a dependable method for the conservation and extensive propagation of this orchid species.